Tren Coffee Vlog: Analisis Sentimen dan Toksisitas Pengguna Sharing Media Platform Youtube terhadap Konten Digital Latte Art dan Beverage Manufacturing - Yerik Afrianto Singgalen (Jurnal Perkotaan, 2024)
This research examines the effectiveness of Coffee Vlogs as a promotional tool to build community and strengthen brand image among urban audiences. The findings show that creative and educational content successfully captures attention and builds strong emotional connections with viewers, while digital media platforms effectively foster engagement and customer loyalty. Toxicity analysis of the first video reveals variations in the levels of comment toxicity. In contrast, sentiment analysis of the second video indicates that most reviews have positive sentiments towards the content. Despite limitations in analyzing viewer behavior and digital media effectiveness, the Digital Content Reviews and Analysis Framework successfully evaluates coffee shop marketing strategies.